A new model of short acceleration‐based training improves exercise performance in old mice. (20th December 2016) - Niel, R.; Ayachi, M.; Mille‐Hamard, L.; Le Moyec, L.; Savarin, P.; Clement, M.‐J.; Besse, S.; Launay, T.; Billat, V. L.; Momken, I.
Abstract: In order to identify a more appealing exercise strategy for the elderly, we studied a mouse model to determine whether a less time‐consuming training program would improve exercise performance, enzyme activities, mitochondrial respiration, and metabolomic parameters. We compared the effects of short‐session (acceleration‐based) training with those of long‐session endurance training in 23‐month‐old mice. The short‐session training consisted of five acceleration‐based treadmill running sessions over 2 weeks (the acceleration group), whereas the endurance training consisted of five‐one‐hour treadmill sessions per week for 4 weeks (the endurance group). A control group of mice was also studied. In the acceleration group, the post‐training maximum running speed and time to exhaustion were significantly improved, relative to pretraining values (+8% for speed, P <.05; +10% for time to exhaustion, P <.01). The post‐training maximum running speed was higher in the acceleration group than in the endurance group (by 23%; P <.001) and in the control group (by 15%; P <.05). In skeletal muscle samples, the enzymatic activities of citrate synthase, lactate dehydrogenase, and creatine kinase were significantly higher in the acceleration group than in the endurance group. Furthermore, mitochondrial respiratory activity in the gastrocnemius was higher in the acceleration group than in the control group. A metabolomic urine analysis revealed a higher mean taurine concentration and a lower mean branched amino acid concentration in the acceleration group. In old mice, acceleration‐based training appears to be an efficient way of increasing performance by improving both aerobic and anaerobic metabolism, and possibly by enhancing antioxidant defenses and maintaining muscle protein balance.